'Brilliant!' : New Art From London. - Flood, Richard; Morgan, Stuart; Wakefield, Neville; Fogle, Douglas; Walker Art Center, Minneapolis; Contemporary Arts Museum, Houston (Minneapolis : Walker Art Center, 1995)
Bond, Henry ; Brown, Glenn ; Chapman, Dinos ; Chapman, Jake ; Chodzko, Adam ; Collishaw, Matt ; Emin, Tracey ; Fairhurst, Angus ; Gallaccio, Anya ; Gillick, Liam ; Hirst, Damien ; Hume, Gary ; Landy, Michael ; Lane, Abigail ; Lucas, Sarah ; Ofili, Chris ; Pippin, Steven ; Raho, Alessandro ; Starr, Georgina ; Taylor-Wood, Sam ; Wearing, Gillian ; Whiteread, Rachel
Walker Art Center, Minneapolis, October 22 1995 - January 7 1996 ; Contemporary Arts Museum, Houston, February 17 - April 14 1996
kunstcatalogus